Studi Pendekatan Bentuk pada Desain Rumah Sakit Khusus Lanjut Usia di Jakarta dengan Tema Arsitektur Biophilic - Depa Tiani (Fakultas Teknik - Universitas Bung Karno, 2023)
This article aims to examine the approach to the design form of a hospital specifically for senior citizens with a Biophilic Architecture approach. Elderly hospitals are based on specific care service needs for senior citizens who require special treatment both psychologically and medically. The Biophilic Architecture design approach was chosen for design oriented towards creating a close relationship between humans as users and their natural environment. Discussion in the design preparation process is based on a descriptive qualitative approach with survey techniques and literature studies. From the results of the discussion, it can be stated that the process of medical treatment for treatment and recovery is the main activity realized in the treatment room, inpatient room and interaction room. The design concept leads to healing environment conditions in the form of a feeling of relaxation, human and comfortable relationships with open spaces in voids, openings, and the unity of supporting spaces in the form of parks integrated in buildings.